Finite element procedure to simulate sandwich structure with an auxetic core under impact loading using ABAQUS/Explicit - Arief Yudhanto; Valdo Pratama; Annisa Jusuf; Bambang Kismono Hadi (Institute of Advanced Engineering and Science, 2023)
A sandwich structure with an auxetic core is promising in improving the performance of a sandwich structure by implying an auxetic core as its core to combine the advantages of the two structures, e.g., sandwich structure’s superior ability in flexural and shear resistance, auxetic structure in localizing damage, and densification phenomena. This paper discusses a finite element modeling procedure to simulate a sandwich structure with a heterogeneous re-entrant auxetic core. The material of the face is a unidirectional carbon fiber reinforced polymer (UD CFRP) and the core is polylactic acid (PLA). The model is subjected to a low-velocity impact loading and is run through the ABAQUS/Explicit software. We found that the model we developed here could simulate up to the elastic region and identify which element had failed. However, it could not fully resemble and represent the model from reference, where fracture or damage does not occur. This model can be further improved in its material modeling strategy, especially in the fracture modeling of the composite face with compatible material properties in all required sectors, especially damaged sections, which are strictly necessary.